Volumetric Absorptive Microsampling as a Sampling Alternative in Clinical Trials and Therapeutic Drug Monitoring During the COVID-19 Pandemic: A Review - Harahap, Yahdiana (Drug Des Devel Ther, 2020)
An infectious disease, COVID-19, caused by a new type of coronavirus, has been discovered recently. This disease can cause respiratory distress, fever, and fatigue. It still has no drug and vaccine for treatment and prevention. Therefore, WHO recommends that people should stay at home to reduce disease transmission. Due to the quarantine, FDA stated that this could hamper drug development clinical trial protocols. Hence, an alternative sampling method that can be applied at home is needed. Currently, volumetric absorptive microsampling (VAMS) has become attention in its use in clinical and bioanalytical fields. This paper discusses the advantages and challenges that might be found in the use of VAMS as an alternative sampling tool in clinical trials and therapeutic drug monitoring (TDM) during the COVID-19 pandemic. VAMS allows easy sampling, can be done at home, storage and delivery at room temperature, and the volume taken is small and minimally invasive. VAMS is also able to absorb a fixed volume that can increase the accuracy and precision of analytical methods, and reduce the hematocrit effects (HCT). The use of VAMS is expected to be implemented immediately in clinical trials and TDM during this pandemic considering the benefits it has.